The Effect of Human Resource Management Quality on Employee Performance at the Banggai Islands Regency Transportation Office - Rahdiyah Unus; Burhanuddin; Sarifuddin. T (Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Palu, 2025)
This study aims to analyze the influence of individual factors (X?) and organizational factors (X?) on employee performance (Y) at the Banggai Islands Regency Transportation Office. The research method used a quantitative approach by distributing questionnaires to 88 employees as respondents. Data were analyzed through validity, reliability, classical assumptions (normality, multicollinearity, heteroscedasticity), and multiple linear regression with the help of SPSS 23. Individual factors (competence, motivation, personality, physical/mental condition) have a positive and significant effect on employee performance (regression coefficient = 0.658; significance 0.000). Organizational factors (leadership, organizational culture, work environment, reward system) also had a significant effect with a coefficient of 0.234 (significance 0.000). Simultaneously, both factors explained 64.6% of the variation in performance (R² = 0.646), while the rest were influenced by external factors. The research instrument was declared valid (item-total correlation > 0.30) and reliable (Cronbach's Alpha > 0.70). The classical assumption test met the requirements of normality, no multicollinearity (VIF < 10), and homocedasticity. The practical implications of this study emphasize the importance of developing individual competencies as well as improving organizational systems to improve employee performance